Camptothecin-loaded mesoporous silica nanoparticles functionalized with CpG oligodeoxynucleotide as a new approach for skin cancer treatment - Qureshi, Munibah (2024)
The therapeutic efficacy of camptothecin (CPT), a potent antitumor alkaloid, is hindered by its hydrophobic nature and instability, limiting its clinical use in treating cutaneous squamous cell carcinoma (SCC). This study introduces a novel nano drug delivery system (NDDS) utilizing functionalized mesoporous silica nanoparticles (FMSNs) for efficient CPT delivery. The FMSNs were loaded with CPT and subsequently coated with chitosan (CS) for enhanced stability and bioadhesion. Importantly, CpG oligodeoxynucleotide (CpG ODN) was attached onto the CS-coated FMSNs to leverage the immunostimulatory properties of CpG ODN, augmenting the chemotherapy's efficacy. The final formulation FMSN-CPT-CS-CpG displayed an average size of 241 nm and PDI of 0.316 with an encapsulation efficiency of 95 %. Comprehensive in vitro and in vivo analyses, including B16F10 cells and DMBA/TPA-induced SCC murine model, demonstrated that the FMSN-CPT-CS-CpG formulation significantly enhanced cytotoxicity against B16F10 cells and induced complete regression in 40 % of the in vivo subjects, surpassing the efficacy of standard CPT and FMSN-CPT treatments. This study highlights the potential of combining chemotherapeutic and immunotherapeutic agents in an NDDS for targeted, efficient skin cancer treatment.